2008
DOI: 10.1002/jmor.10622
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of hatching and early post‐embryonic life of freshwater crayfish by in vitro culture, behavioral analysis, and light and electron microscopy

Abstract: The late embryonic and early post-embryonic life period of freshwater crayfish, which is the main time period of organogenesis, is poorly investigated because of the protective brooding behavior of crayfish mothers. A combination of in vitro culture, behavioral observations, and microscopic investigations of organs involved in hatching, attachment, exploration of the environment, and searching and processing of food yielded deeper insights in this important period of life. Experiments were performed with the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 47 publications
0
64
0
Order By: Relevance
“…For instance, the sternal artery, which connects the heart to the ventral thoraco-abdominal artery, can be either paired and bilateral symmetric, or unpaired and right or left asymmetric, as revealed by serial sectioning of more than 100 juveniles (Vogt et al, manuscript submitted for publication). Movement patterns and social behaviours were shown to vary considerably among stage-2 batch-mates raised from in vitro cultured eggs (Vogt, 2008). And the duration of embryonic development, hatching success, growth of the juveniles, and grade of malformation of the appendages varied considerably among sibs exposed in 12-well micro-plates to 100·g·l…”
Section: Perspectivesmentioning
confidence: 99%
“…For instance, the sternal artery, which connects the heart to the ventral thoraco-abdominal artery, can be either paired and bilateral symmetric, or unpaired and right or left asymmetric, as revealed by serial sectioning of more than 100 juveniles (Vogt et al, manuscript submitted for publication). Movement patterns and social behaviours were shown to vary considerably among stage-2 batch-mates raised from in vitro cultured eggs (Vogt, 2008). And the duration of embryonic development, hatching success, growth of the juveniles, and grade of malformation of the appendages varied considerably among sibs exposed in 12-well micro-plates to 100·g·l…”
Section: Perspectivesmentioning
confidence: 99%
“…Several important characteristics of marbled crayfish have been described in detail, including morphology (Kawai et al, 2009), embryonic development (Alwes & Scholtz, 2006;Seitz et al, 2005), life history (Seitz et al, 2005;Vogt, 2008;Vogt et al, 2004), parthenogenetic reproduction (Martin et al, 2007;Scholtz et al, 2003;Vogt et al, 2008) and a triploid karyotype . Using morphological characters and molecular markers, Martin et al identified the sexually reproducing slough crayfish Procambarus fallax from Florida as the closest relative of marbled crayfish and suggested the provisional name Procambarus fallax forma virginalis (Martin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It will be the challenge of future investigations to identify the epigenetic and molecular mechanisms that cause this symmetry variation. Because its embryos and early juveniles can be cultured in simple facilities, including microplates (Vogt, 2007(Vogt, , 2008a, the marbled crayfish may serve as an additional model to investigate the establishment and maintenance of bilateral symmetry and symmetry breaking in metazoans (Mercola and Levin, 2001;Palmer, 2004). Future studies using marbled crayfish raised under different experimental conditions could provide information on the modifiability of symmetry by the macroenvironment, and experiments with the sexually reproducing and closely related species, either Procambarus alleni or Procambarus fallax, could provide information on the genetic aspects of symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…The parthenogenetic marbled crayfish, which was discovered in the mid 1990s (Scholtz et al, 2003;Vogt, 2008b), seems to be a particularly suitable candidate for a detailed investigation into this problem as it is the only known decapod crustacean to produce genetically identical offspring (Martin et al, 2007;Vogt et al, 2008). Moreover, this crayfish develops directly without metamorphosis Alwes and Scholtz, 2006) and can be reared in very simple environments including microplates (Vogt, 2007(Vogt, , 2008a. To examine whether symmetry variation in the descending artery of crayfish is the result of developmental variation we serial-sectioned isogenic embryos and early juveniles of marbled crayfish raised under identical environmental conditions.…”
mentioning
confidence: 99%